Análisis de la ejecución presupuestal y el cumplimiento de las metas en la Municipalidad Distrital de Punchana en el periodo 2018 – 2022 - Vasquez Aspajo, Alaska Scarlette (2024)
This research focused on budget execution and achievement of goals of the district municipality of Punchana during the periods 2018-2022, identifying existing challenges and proposing recommendations to improve efficiency in the public management of the entity. The main objective is to contribute to the development of policies and strategies that promote equitable access to the population's progress and improve the basic conditions of the district. To achieve this purpose, an exhaustive review of the existing literature on the subject was carried out, considering the economic and financial implications of the results obtained. In this context, 18 observations corresponding to the period 2018-2022 were analyzed, covering budget execution from various sources of financing, both income and expenses, with the objective of evaluating the fulfillment of goals in the district municipality of Punchana. As a result of this analysis, it was concluded that there is a very strong positive relationship of 99.38% between the variables studied. In other words, when budget execution is efficient, a corresponding level of efficiency is observed in achieving budget goals.